The leukemogenic fusion gene MLL-AF9 alters microRNA expression pattern and inhibits monoblastic differentiation via miR-511 repression. Issue 1 (December 2016) - Fleischmann, Katrin; Pagel, Philipp; von Frowein, Julia; Magg, Thomas; Roscher, Adelbert; Schmid, Irene
Abstract Background In this study we explored the role of microRNAs (miRNAs) as mediators of leukemogenic effects of the fusion geneMLL-AF9, which results from a frequent chromosomal translocation in infant and monoblastic acute myeloid leukemia (AML). Methods We performed a specific and efficient knockdown of endogenousMLL-AF9 in the human monoblastic AML cell line THP1. Results The knockdown associated miRNA expression profile revealed 21MLL-AF9 dependently expressed miRNAs. Gene ontology analyses of target genes suggested an impact of these miRNAs on downstream gene regulation via targeting of transcriptional modulators as well as involvement in many functions important for leukemia maintenance as e.g. myeloid differentiation, cell cycle and stem cell maintenance. Furthermore, we identified one of the most intensely repressed miRNAs, miR-511, to raiseCCL2 expression (a chemokine ligand important for immunosurveillance), directly target cyclin D1, inhibit cell cycle progression, increase cellular migration and promote monoblastic differentiation. With these effects, miR-511 may have a therapeutic potential as a pro-differentiation agent as well as in leukemia vaccination approaches. Conclusions Our study provides new insights into the understanding of miRNAs as functional mediators of the leukemogenic fusion geneMLL-AF9 and opens new opportunities to further investigate specific therapeutic options for AML via the miRNA level.